Psychosocial issues and concerns of cancer patients due to COVID-19 pandemic lockdown - Surendran Veeraiah; Sundaramoorthy Chidambaram; Revathy Sudhakar; Selvaluxmi Ganesharaja; Arvind Krishnamurthy; Manikandan Dhanushkodi; Rajaraman Swaminathan (PLOS Global Public Health, 2022)
Background The COVID-19 pandemic lockdown has posed numerous unique challenges for cancer patients, families and healthcare workers. However, the reports on psychosocial issues associated with such situations are scarce. This study aims to determine the psychosocial issues faced by cancer patients during COVID-19 pandemic lockdown. Methods Cancer patients irrespective of diagnosis and treatment status were assessed for fear of progression (FOP), distress and quality of life (QOL) using Fear of Progression- Short Form, Distress Thermometer and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ C30) 30, respectively. The demographics, disease and treatment related details were obtained from case record form. Psychological issues and concerns were collected using a structured interview. Descriptive statistics, Mann Whitney U-test and Linear Regression were performed using SPSS ver 20.0. Results Among the 219 patients, 118 (52.5%) had either interruption in their on-going cancer treatment or the initiation of cancer treatment was delayed as a result of COVID-19 lockdown. Overall, 74% of the patients experienced distress, 55.3% experienced FOP and 58% had low global health status. Pain followed by fatigue remained as major issues among patients during lockdown. Interruption in treatment and logistical issues were strongly associated with increased distress (p = 0.026) and FOP (p = 0.004). Global health status (p = 0.037), emotional functioning (p = 0.000), social functioning (p = 0.000) and financial concerns (p = 0.046) differed significantly between patients with and without treatment interruption. Age (β = -0.159), mode of transport (β = -0.135), challenges in meeting daily needs (β = -0.245) and being out-casted by the society (β = -0.227) predicted distress. Conclusion More than half of the patients had interruptions in their treatment as a result of COVID-19 lockdown. Cancer patients have had increased physical and psychological concerns as a result of the pandemic situation and its associated changes. Specific guidelines ought to be framed for providing continued and holistic cancer care for patients during such lockdown.